Photopolymerization of thiol-alkynes: Polysulfide networks - Chan, J.; Zhou, H.; Hoyle, C.; Lowe, Andrew (American Chemical Society, 2009)
A series of photoinitiated reactions involving radical chain addition of dithiols across the triple bonds of dialkynes results in quantitative loss of all of the thiol and alkyne groups in 1:1 molar functional group neat mixtures. The reactions proceed rapidly to give uniform networks with relatively narrow differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) glass transition ranges. The glass transitions of the network films are directly related to the network structure and range from below 0 C° to about 40 C° as determined by DMA. The thiol-alkyne based hydrocarbon networks with sulfide linking groups have refractive index values which extend as high as 1.66. There is a linear relationship between the density and the refractive index, both of which increase linearly with weight percent sulfur. © 2009 American Chemical Society.